The Bender Gestalt Test: an investigation into problems concerning administration and scoring and its application to low-educated adults - Dyall, Kate (Rhodes University, Faculty of Humanities, Department of Psychology, 1996)
The study investigates .the use of the Bender Gestalt Test (BGT) amongst low-educated adults. Three versions of the BGT are used in this study; the original 'copy' version as well as the 'immediate' and 'delayed'recall versions. This is done so as to expand the ability of the BGT to identify neurological impairment and to differentiate between this and functional impairment. A literature review explores the problems of standardization in the administration, scoring and application of all three versions of the test Suggestions are made to correct the problems identified and a novel system of scoring the recall versions are proposed, which allows for the comparison of results of the three versions of the test and which is based on Lacks's (1984) and Weiss's (1970) systems. Administration procedures were also developed to suit the context of the study. The copy, immediate and delayed versions of the BGT were administered to a group of 184 low-educated adults. Statistical analyses revealed significant education effects for the sample tested with regards to both test scores and performance time. The finding of an education effect for performance time is discussed at length, as some literature regards excessive time as a neurological indicator. An anomaly for the group with no education was found to exist, with the scores of these subjects not Significantly different from those with 4-6 years of education. Possible reasons for this were explored. In addition, the findings of this research revealed a plateau effect with those having less than 6 years of education scoring substantially lower than those with 7 years and more. The scores of adults with 7 and more years of education level out with no significant differences between educational levels. This appears to suggest that education effects rather than the developmental maturity level proposed by Koppitz, are involved. In addition, the scores of low-educated adults on the expanded Bender Gestalt Test were significantly lower than those of children with similar educational levels, in other studies. These findings and possible explanations are discussed. The study concludes by suggesting new research areas and emphasizing the urgent need for separate normative data on the expanded BGT for low-educated adults, and the establishment of appropriate 'cut-off' points.
Keywords: Bender-Gestalt Test; Psychological tests; Brain-damaged children -- Psychological testing